The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/membranes11050344
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Non-Constancy of the Bulk Resistance of Ion-Selective Electrode Membranes within the Nernstian Response Range

Abstract: The dependence of the bulk resistance of membranes of ionophore-based ion-selective electrodes (ISEs) on the composition of mixed electrolyte solutions, within the range of the Nernstian potentiometric response, is studied by chronopotentiometric and impedance measurements. In parallel to the resistance, water uptake by the membranes is also studied gravimetrically. The similarity of the respective curves is registered and explained in terms of heterogeneity of the membranes due to the presence of dispersed aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Depletion of primary ions from the sample solution|ISM interface was successfully slowed due to the increased tortuosity of the pathway for ions to enter the bulk of the ISM. , The proposed ISEs showed extended Nernstian linear ranges down to 10 – 8 mol dm –3 . A similar explanation for a tortuous charge-transfer pathway was recently proposed for water droplets within the ISM organic phase. In this work, we show that the introduction of foamlike structures (network of bubbles) near the SC|ISM interface can similarly tailor ion flux in ISMs. The bubbles originated from the ISM|solid contact (SC) interface after ISM cocktail deposition onto the SC of screen-printed electrodes that were held at a temperature near to the boiling point of the ISM cocktail solvent.…”
supporting
confidence: 83%
“…Depletion of primary ions from the sample solution|ISM interface was successfully slowed due to the increased tortuosity of the pathway for ions to enter the bulk of the ISM. , The proposed ISEs showed extended Nernstian linear ranges down to 10 – 8 mol dm –3 . A similar explanation for a tortuous charge-transfer pathway was recently proposed for water droplets within the ISM organic phase. In this work, we show that the introduction of foamlike structures (network of bubbles) near the SC|ISM interface can similarly tailor ion flux in ISMs. The bubbles originated from the ISM|solid contact (SC) interface after ISM cocktail deposition onto the SC of screen-printed electrodes that were held at a temperature near to the boiling point of the ISM cocktail solvent.…”
supporting
confidence: 83%
“…On the other hand, although each individual curve can be nicely fitted to Equation (3), the fitted parameters R Mem , C CP , and N vary from one individual curve to another. In particular, for R Mem the membrane bulk resistance depends on the concentration of the solution and correlates with sorption of water by membranes [ 19 , 20 , 21 , 22 , 23 , 24 ]. Because of this variation, the use of the respective average values obtained in calibration solutions (0.25, 0.5, 1, 2, 4, 8 mM) results in scattering in the sample analysis data, as discussed in Section 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that water droplets in membranes hamper the diffusion of lipophilic ion-ionophore complexes and ion-exchangers because lipophilic species are confined to the coherent organic phase in the membrane, and have to bypass the water droplets, so their average path length increases. Thus, the concentration of the species in the organic phase of the membrane is constant ensuring the Nernstian response of the ISE, while the resistance increases along with the increased sorption of water [48,53].…”
Section: Studies Of the Mechanism Of The Ise Potentiometric Response ...mentioning
confidence: 99%
“…It may appear that these findings are of only academic interest. It was shown, however, that water uptake and the bulk resistance of ISE membranes actually depends on the ionic strength of the solution, or on the total concentration of ions, rather than on the concentration of the respective primary ion [53]. This offers a prospect of measurements of not only activities but also of concentrations of ions by the same sensor.…”
Section: No −mentioning
confidence: 99%